THE EFFECTIVENESS OF DIGITAL COMICS (DC) IN THE TEACHING OF WRITING RECOUNT TEXTS - Nur Faiza Layla (Language-Edu, 2020)
This research is goaled at measuring the effectiveness of digital comics (DC) in teaching of writing recount texts at eighth of SMPN 2 Krian Sidoarjo. A complex activity is teaching writing than the other. There are same aspects that should be understood such as grammar, punctuation and spelling, organization, cohesive and coherent devices and vocabulary. Therefore, the teachers should have a great interest, selection of media and strategies in writing activities. The objectives of the study are (1). to describe the process of teaching and learning writing skill of recount text, (2). to know of the problems faced by the teacher and the students in teaching learning writing skill of recount text. Recount text which retells experiences or happens in the last. A recount text owns an orientations, a kind of happens in chronological messege, personal remarks on the happens, and re orientation which the sequence of events.It can be concluded that teaching writing of recount texts using by digital comics is more useful and effective to be taught to the eighth class students of SMPN 2 Krian Sidoarjo. It can also be seen from the calculation and the table of students’ achievement from their writing score in pre-test and post test by using digital comics is higher than the students’ writing score. Therefore, digital comic can be an appropriate media that can be recommended in teaching writing of recount text. Especially for the eighth class students of SMPN 2 Krian Sidoarjo in academic year 2018/2019.Keywords: Digital Comics (DC), Writing Recount Texts.